PENGARUH METACOGNITIVE AWARENESS TERHADAP HASIL BELAJAR - Myeka Fitri Swarnadwi; Neti Budiwati; Siti Parhah; Fazar Nuriansyah (Jurnal Pendidikan Ekonomi Indonesia, 2021)
This research is motivated by student learning outcomes that have not been optimal, as indicated by the average GPA of FPEB UPI students has not reached the target stated in the 2016-2020 UPI Strategic Plan. This study aims to see the effect of metacognitive awareness on learning outcomes. In addition, this study also examines the direct influence of the two domains contained in metacognitive awareness, namely metacognitive knowledge (knowledge of cognition) and metacognitive control (regulation of cognition) on learning outcomes. The population in this study were all students of FPEB UPI class 2017, 2018, and 2019 with a sample of 329 students. The method used in this study is an explanatory survey with multiple linear regression analysis techniques. The results showed that metacognitive awareness had a positive effect on learning outcomes. In addition, it was also found that two domains in metacognitive awareness, namely metacognitive knowledge (knowledge of cognition) and metacognitive control (regulation of cognition) had a positive effect on improving learning outcomes.